Sistem Pengambilan Keputusan Prioritas Surat Bantuan Dana Untuk Pendidikan Dengan Metode Top Down Parsing - Ilhami, A.Mika; Hadiansyah, M. Nauval Hafizh; Baihaqi, Abdullah Afif; Khalid, Ikhsan Putra (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2024)
This research proposes and applies a decision-making system to determine priorities in the allocation of educational funding assistance letters by utilizing the Top-Down Parsing method. The aim of this research is to increase efficiency in managing the allocation of education funds through the implementation of parsing technology for analysis and processing of letters requesting financial assistance. This system is designed to automatically analyze sentence structures, identify relevant information, and determine funding allocation priorities based on predetermined criteria. Through simulation experiments, this research evaluates the effectiveness and accuracy of the system in prioritizing letters requesting funding for education. The research results show that the application of the Top-Down Parsing method in the decision-making system is able to increase efficiency in the education fund allocation process. Nonetheless, this research highlights the need for regular maintenance and updating to maintain analytical accuracy.